Central role for p62/SQSTM1 in the elimination of toxic tau species in a mouse model of tauopathy. Issue 7 (5th June 2022) - Ono, Maiko; Komatsu, Masaaki; Ji, Bin; Takado, Yuhei; Shimojo, Masafumi; Minamihisamatsu, Takeharu; Warabi, Eiji; Yanagawa, Toru; Matsumoto, Gen; Aoki, Ichio; Kanaan, Nicholas M.; Suhara, Tetsuya; et al.
Abstract: Intracellular accumulation of filamentous tau aggregates with progressive neuronal loss is a common characteristic of tauopathies. Although the neurodegenerative mechanism of tau‐associated pathology remains unclear, molecular elements capable of degrading and/or sequestering neurotoxic tau species may suppress neurodegenerative progression. Here, we provide evidence that p62/SQSTM1, a ubiquitinated cargo receptor for selective autophagy, acts protectively against neuronal death and neuroinflammation provoked by abnormal tau accumulation. P301S mutant tau transgenic mice (line PS19) exhibited accumulation of neurofibrillary tangles with localization of p62 mostly in the brainstem, but neuronal loss with few neurofibrillary tangles in the hippocampus. In the hippocampus of PS19 mice, the p62 level was lower compared to the brainstem, and punctate accumulation of phosphorylated tau unaccompanied by co‐localization of p62 was observed. In PS19 mice deficient in p62 (PS19/p62‐KO), increased accumulation of phosphorylated tau, acceleration of neuronal loss, and exacerbation of neuroinflammation were observed in the hippocampus as compared with PS19 mice. In addition, increase of abnormal tau and neuroinflammation were observed in the brainstem of PS19/p62‐KO. Immunostaining and dot‐blot analysis with an antibody selectively recognizing tau dimers and higher‐order oligomers revealed that oligomeric tau species in PS19/p62‐KO mice were significantly accumulated as compared to PS19 mice, suggesting the requirement of p62 to eliminate disease‐related oligomeric tau species. Our findings indicated that p62 exerts neuroprotection against tau pathologies by eliminating neurotoxic tau species, suggesting that the manipulative p62 and selective autophagy may provide an intrinsic therapy for the treatment of tauopathy. Abstract : This study proposes a mechanism that p62/SQSTM1, a ubiquitinated cargo receptor for selective autophagy, acts protectively against neuronal death and neuroinflammation as tau pathologies by eliminating disease‐related oligomeric tau formed during the aggregation process of abnormal tau.